Strength and microstructural properties of mortar containing soluble silica from sugarcane bagasse ash - Andri, Kusbiantoro; Rahimah, Embong; Azrina, Abd Aziz (Trans Tech Publications Ltd., 2018)
Sugarcane bagasse is among the abundantly available waste in agriculture industry. The proportion of siliceous ashes after the incineration process is one of the attractive features in sugarcane bagasse. However, its low bulk density would result in an additional issue for further use as cement replacement material, since higher replacement volume will bring more hydrophilic particles of sugarcane bagasse ash into the mixture. Therefore this research aims to extract the reactive silica from sugarcane bagasse ash and increase its bulk density by converting it into soluble form. The process was divided into three stages, which were pre-treatment and incineration of sugarcane bagasse, conversion into soluble form, and production of mortar specimen. Soluble silica from sugarcane bagasse ash was used to partially replace cement content in mortar, hence its effect on the hydration process can be evaluated. Compression test and scanning electron microscope analysis were performed to observe its effect on the strength and microstructural development of mortar framework. The results show that the inclusion of soluble silica would enhance the early hydration rate and improve the consolidation of cement matrix via additional calcium silicate hydrate formation, which would increase the capability of internal mortar framework to distribute loads and achieve higher strength.